EFEK FERRI SITRAT TERHADAP KEMAMPUAN KHAMIR Candida tropicalis DALAM MEREDUKSI 3-(4,5-DIMETHYLTHIAZOL-2-YL)- 2,5-DIPHENYLTETRAZOLIUM BROMIDE (MTT) [Effect of ferric citrate on 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) reduction in yeast Candida tropicalis] - Julistiono, Heddy; Muthmainah, Resti Siti; Adam, Adam (BERITA BIOLOGI, 2012)
Effect of iron (ferric citrate) on 3-(4,5-dimethylthiazol-2-yl)2,5-diphenyltetrazolium bromide (MTT) reduction in yeast Candida tropicalis was investigated. Reduction of MTT in yeast grown in YMB media containing 5 mM of ferric citrate decreased significantly compared to that of yeast grown containing 0, or 1.25 or 2.5 mM ferric citrate after 24 h incubation. However, there was no difference in cell density among cultures treated with 0 mM, 1.25 mM, and 5 mM ferric citrate. Ferric citrate of 5 mM caused smaller colony when cells were grown on YPDG media. Reduction of MTT in smaller colony cells was weaker than that of with normal size colony. An antioxidant, Epigallocatechin Gallate (EGCG) of 0.01 % could not reverse MTT reduction caused by 5 mM ferric citrate. Since enzymes responsible in MTT reduction are usually located in mitochondrion, the data suggested that, in the condition of 5 mM ferric citrate might cause mitochondrion disorder without killing the yeast cells. The data was in concordance with other studies on other yeast or human cells. However, this study does not show role of free radicals provoked by high level of iron concentration.